Integrating Civic Education Curriculum With Islamic Moral Principles For Character Formation Among Secondary School Students In Zamfara State, Nigeria - Sule Muhammad; Sabiu Lawal (Penerbit Hellow Pustaka, 2025)
This study examined the effect of integrating Civic Education with Islamic moral principles on students’ moral behaviour, civic responsibility, discipline, and social harmony among secondary school students in Zamfara State, Nigeria. The study adopted a quantitative research approach using a descriptive survey design to collect data from 384 respondents, including Civic Education and Islamic Studies teachers. A structured questionnaire titled Integration of Civic and Islamic Moral Education Questionnaire (ICIMEQ) was developed and validated by experts, with a reliability coefficient of 0.88 obtained using Cronbach Alpha. Data were analyzed using both descriptive and inferential statistics such as mean, standard deviation, Pearson Product Moment Correlation (PPMC), and independent t-test at a 0.05 level of significance. The findings revealed a strong and significant positive relationship between the integration of Civic and Islamic moral principles and students’ moral behaviour, civic responsibility, discipline, and social harmony (r = .612, p < .05). Results also showed that teachers generally perceived the integration as relevant and practical, although Civic Education teachers recorded slightly higher mean scores than Islamic Studies teachers (t = 3.28, p = .001). This implies that blending Civic Education content with Islamic moral teachings effectively promotes ethical conduct, social harmony, and responsible citizenship among students. The study’s findings align with Bandura’s Social Learning Theory and Kohlberg’s Moral Development Theory, which emphasize learning through moral reasoning, observation, and value internalization. The study concluded that integrating Civic Education with Islamic moral principles offers a holistic framework for character formation and nation-building. It was recommended that curriculum planners, policymakers, and teachers adopt this integrated approach to strengthen moral education, promote discipline, and enhance civic values among Nigerian students.